Effect of Emotional Intelligence on Leadership Effectiveness in Nepalese Commercial Banks - Bhandari, Mohan; Tiwari, Ghanashyam; Dhakal, Maheshwor (Journal of Business and Management, 2024)
Background: Emotional intelligence plays a vital role in enhancing leadership effectiveness, particularly in fostering decision-making and interpersonal skills within Nepalese commercial banks. Objectives: The objective of this study is to explore the impact of emotional intelligence on leadership effectiveness. The study focuses on its implications for the managerial performance of managers in Nepalese commercial banks. Methods: A positivist (quantitative) survey study was employed in this investigation. Descriptive and inferential analysis were employed for the conclusions and findings of the study. Using multistage sampling, 221 workers from particular commercial banks in Nepal were chosen as a sample. The survey questionnaire was used to measure emotional intelligence in five different variables and leadership assessment through decision-making, vision, and value creation using SPSS 26 and Smart PLS-3. Results: The study concludes a positive relationship between overall EI and LE. Social awareness is the top predictor of EI in leadership. Employees with high EI show better leadership effectiveness. Conclusion: Emotional Intelligence is considered crucial for leaders and can be developed to improve leadership effectiveness. Leadership development programs in banks should emphasize EI training for aspiring and current leaders. Improved leaders’ EI can help to create a positive work environment. More harmony and support may be found in the workplace when leaders possess strong communication skills and a keen sense of social awareness. JEL Classification: D91, M12, O15